Assessment of rational use of drugs and self-medication in Turkey: A pilot study from Elazig and its suburbs - Nayir, Tufan; Okyay, Ramazan Azim; Yesilyurt, Hakki; Akbaba, Muhsin; Nazlican, Ersin; Acik, Yasemin; Akkus, Halil Ibrahim (Univ Karachi, 2016)
The concepts of essential drugs and national drug policy described by the World Health Assembly in 1975 were the first steps taken towards the rational use of drugs (RUD). According to WHO, more than half of all medicines worldwide are prescribed, dispensed or sold inappropriately and half of the patients fail to take them appropriately. The aim of this study has been to evaluate the habits of patients related to RUD with a specific aim to investigate the factors associated with self-medication. This descriptive survey study was carried out in Elazig, located at the Southeastern region of Turkey. A Rational Usage of Drug Questionnaire, querying the socio-demographic characteristics, health status, knowledge and manners of people with respect to rational drug use and insensible consumption of over the counter (OTC) drugs was applied to a total of 3521 patients during 19.09.2014 to 26.09.2014. The number of females and males were almost equal and the majority were in the range of 25-45 years of age. It was found that 58.9% of patients were practising some form of self-medication, 29.4% of the patients were reported using antibiotics without prescriptionand55.5% of them discontinued antibiotherapy. Self-medication was found to be more common among males, more educated patients and less frequent among patients under 1-8 years and over 65 years of age and patients with a chronic disease. Patient awareness about RUD is inadequate in Turkey as in many countries. Considering the high rates of haphazard use of drugs, drug usage without prescription, i.e. OTC drugs, should be discouraged. It is possible to take significant steps towards increasing awareness in terms of RUD with the cooperation of physicians, health organizations, educational institutions, non-governmental organizations and media. Might then be possible to achieve the expected benefits of the drugs.
Keywords: Rational use of drugs; Self medication; Pharmacoepidemiology; Turkey